2015
DOI: 10.1089/scd.2014.0490
|View full text |Cite
|
Sign up to set email alerts
|

Transplanted Umbilical Cord Mesenchymal Stem Cells Modify the In Vivo Microenvironment Enhancing Angiogenesis and Leading to Bone Regeneration

Abstract: Umbilical cord mesenchymal stem cells (UC-MSCs) show properties similar to bone marrow mesenchymal stem cells (BM-MSCs), although controversial data exist regarding their osteogenic potential. We prepared clinical-grade UC-MSCs from Wharton's Jelly and we investigated if UC-MSCs could be used as substitutes for BM-MSCs in muscoloskeletal regeneration as a more readily available and functional source of MSCs. UCMSCs were loaded onto scaffolds and implanted subcutaneously (ectopically) and in critical-sized calv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 60 publications
3
63
0
1
Order By: Relevance
“…In our study, newly formed vessels were evidently observed in the defects filled with the UC‐MSCs/scaffolds. These findings are in agreement with prior research in which MSCs derived from human umbilical cord significantly increased ingrowth of blood vessels in vivo compared to MSCs derived from bone marrow . Regeneration of new vessels in damaged sites is always considered as a very important issue in tissue regeneration, because new vessels are responsible for the transportation of nutrients and waste materials .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, newly formed vessels were evidently observed in the defects filled with the UC‐MSCs/scaffolds. These findings are in agreement with prior research in which MSCs derived from human umbilical cord significantly increased ingrowth of blood vessels in vivo compared to MSCs derived from bone marrow . Regeneration of new vessels in damaged sites is always considered as a very important issue in tissue regeneration, because new vessels are responsible for the transportation of nutrients and waste materials .…”
Section: Discussionsupporting
confidence: 91%
“…There was no woven bone tissue in the defects filled with the blank scaffold. These data are consistence with previous studies showing higher osteogenic differentiation potential of MSCs derived from bone marrow compared to other MSCs . Moreover, previous studies conducted on animals showed that the implantation of BM‐MSCs together with bioceramic‐based biomaterials lead to better results .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Most importantly, the authors used 'MSCs' from the umbilical cord (UC), which are very different from the fibroblasts derived from CB that we used in this study (Reinisch et al, 2015). In particular, UC cells are not able to form bone in vivo, even when transplanted with an osteoconductive carrier (Kaltz et al, 2008;Todeschi et al, 2015). Moreover, significant differences have been found in the global gene expression profile of UC-derived cells and CB-BFs isolated from the same donor and cultured under the same culture conditions (Secco et al, 2009).…”
Section: Human Developmentmentioning
confidence: 99%
“…An interconnected porous structure is attractive for bone substitutes because bone tissue and cells can penetrate the bone substitute . Furthermore, microporous structure should play an important role in cell growth and differentiation, similar to the niche environment or microenvironment produced by the extracellular matrix . Among many porous structures available, the honeycomb (HC) structure is unique due to its fully interconnected and oriented pores having the same pore size, and shows high mechanical strength in the direction of the pores …”
Section: Introductionmentioning
confidence: 99%